Facilitating the dissemination of interprofessional education and practice using an innovative conference approach to engage stakeholders - Brewer, Margo (2016)
Significant change is needed to successfully embed interprofessional education (IPE) and interprofessional practice (IPP) within health systems. Change such as this requires effective leadership, yet leadership is an underdeveloped area in IPE and IPP. To address this gap Curtin University drew on organizational change literature, particularly Kotter's (1995) [8] eight-stage change process, to inform the implementation of its large scale IPE curriculum. This paper describes the University's dissemination strategy which is informed by Roger's (2003) [9] 'diffusion of innovation' theory. The success of this strategy was tested on a local IPE conference. Two thirds of the 2014 conference participants (n = 100) completed a short post-conference questionnaire. Seventy-seven to 93 per cent of participants agreed that the conference was informative, applicable, and increased their knowledge of IPE and IPP. The results of this study suggest that 'diffusion of innovation' is a useful theory to inform the dissemination of IPE and IPP.